The Effects of Store Attributes toward Satisfaction and Purchase Intention - Fidelia Hartono; Suresh Kumar (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
With the tight competition among retailers that causes many retail stores are closing down around the world, not to mention Indonesia, hence there is a need to find ways how not only to sustain from the competition but also to become the market leader. Therefore, this study would like to address how to increase sales by gaining more customers through satisfaction and purchase intention using store attributes especially in the supermarket industry. This study uses store attributes, satisfaction, and purchase intentions as its constructs. Therefore, a primary survey was conducted by using a questionnaire that is spread through social media. The questionnaire consists of screening questions, demographic profiles, and the questions regarding the constructs with 51 statements to measure store attributes, satisfaction, and purchase intention. This study uses 367 valid respondents that are gathered using purposive sampling. The data are analyzed using statistical software. Through this study, it shows that store attributes influence satisfaction also satisfaction influences purchase intention. However, store attributes do not influence purchase intention directly, therefore store attributes would only have an impact once the customers are satisfied. This study would like to study how certain dimensions of in-store attributes would influence satisfaction and purchase intention. The dimensions that this study used are adapted from previous studies with various industries in various countries to create a new finding upon the supermarket industry in Indonesia. The findings can be useful for managers of supermarkets as well as investors in order to retain more customers in the future. Since this study was conducted in Greater Jakarta, Indonesia, hence it is not to be generalized to other cities in Indonesia due to cultural differences not to mention other countries.